Faktor Risiko dan Komplikasi Hipertensi Tidak Terkontrol di Indonesia: Literature Review - Nabila Puspitasari; Ade Yonata; Suryadi Islami (Medula, 2026)
Uncontrolled hypertension is one of the major public health problems in Indonesia and contributes substantially to increased morbidity and mortality related to cardiovascular disease and target organ damage. This condition occurs when blood pressure remains above the recommended target despite the use of antihypertensive therapy. This article aims to review and analyze risk factors and complications associated with uncontrolled hypertension in the Indonesian population. The study applied a literature review design with article searches conducted through the Google Scholar and Garuda databases in accordance with the PRISMA 2020 guidelines. Following the selection process, twelve articles met the inclusion criteria and were analyzed descriptively. The review results indicate that the dominant risk factors for uncontrolled hypertension include older age, obesity, diabetes mellitus, dyslipidemia, employment status, low educational level, poor medication adherence, excessive salt intake, physical inactivity, smoking, and psychological stress. The most frequently reported complications were stroke, chronic kidney disease, heart failure, myocardial infarction, and hypertensive retinopathy. These findings demonstrate that uncontrolled hypertension in Indonesia remains a serious challenge that requires integrated control strategies through early detection, optimization of therapy, improvement of patient adherence, and strengthening of promotive and preventive interventions based on primary health care services and community involvement.